2009
DOI: 10.1901/jaba.2009.42-315
|View full text |Cite
|
Sign up to set email alerts
|

Therapist‐ and Self‐monitored Dro Contingencies as a Treatment for the Self‐injurious Skin Picking of a Young Man With Asperger Syndrome

Abstract: The use of differential reinforcement of other behavior (DRO) has decreased, at least partially due to the development of less effortful alternative behavioral interventions (e.g., noncontingent reinforcement; Vollmer, Iwata, Zarcone, Smith, & Mazaleski, 1993). The effort associated with DRO contingencies may be lessened by incorporating self‐monitoring components in which clients are responsible for the delivery of reinforcers for their own behavior. The current study evaluates the effectiveness of DRO in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 14 publications
2
33
0
Order By: Relevance
“…Self-monitoring in this study showed similar effects to teacher monitoring, as did studies of Tiger et al (2009) and Hoff and Ervin (2013). Self-monitoring is an efficient technique that promotes generalization (Stokes & Baer, 1977).…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Self-monitoring in this study showed similar effects to teacher monitoring, as did studies of Tiger et al (2009) and Hoff and Ervin (2013). Self-monitoring is an efficient technique that promotes generalization (Stokes & Baer, 1977).…”
Section: Discussionsupporting
confidence: 72%
“…Any intervention that can increase a student's ability to manage and monitor his or her own behavior would, at least conceptually, decrease a teacher's workload. Tiger, Fisher, and Bouxsein (2009) decreased self-injurious skin picking in an adolescent with Asperger syndrome. A study by McCurdy and Shapiro (1992) demonstrated differential effects of teacher-monitoring, peer-monitoring, and selfmonitoring interventions on reading skills of students with learning disabilities.…”
Section: Self-monitoring Interventionsmentioning
confidence: 95%
“…In the case of an individual with SIB, reinforcement would be delivered if the individual did not engage in SIB throughout the time interval. DRO has been shown to be effective at reducing SIB 77,8486. These positive results may be improved in cases where the reinforcer maintaining SIB is appropriately identified, reinforcers selected are able to compete with the reinforcement maintaining SIB, and when a variety of reinforcers are utilized 85…”
Section: Behavioral Treatments Of Sibmentioning
confidence: 99%
“…These areas include the reduction of tissue-damaging self-injurious behavior with individuals with developmental disabilities (e.g., McGinnis, Houchins-Juárez, McDaniel, & Kennedy, 2010;Tiger, Fisher, & Bouxsein, 2009;Toussaint & Tiger, 2012), dental hygiene (e.g., Barnoy, Najdowski, Tarbox, Wilke, & Nollet, 2009;Lang et al, 2013), treatment of problem behavior and skill acquisition in individuals with brain injury (e.g., Fienup, Ahlers, & Pace, 2011;Guercio, Johnson, & Dixon, 2012;Travis & Sturmey, 2010), treatment of Tourette's syndrome (e.g., Capriotti, Brandt, Ricketts, Espil, & Woods, 2012;Wiskow & Klatt, 2013), obesity (e.g., Hustyi, Normand, & Larson, 2011;Hustyi, Normand, Larson, & Morley, 2012;Shayne, Fogel, Miltenberger, & Koehler, 2012), smoking cessation (e.g., Dallery & Raiff, 2011) and inappropriate sexual behavior (e.g., Reyes, Vollmer, & Hall, 2011a;Reyes, Vollmer, & Hall, 2011b). According to our analysis, ABA conducted in a medical setting (e.g., medical adherence) would be considered behavioral medicine as long as there is an underlying biological condition of the organism that is somehow altered as a result of compliance with the prescribed regimen.…”
Section: The Relationship Between Applied Behavior Analysis and Behavmentioning
confidence: 99%